Analisls Strategl Pemasaran Untuk Menlngkatkan Penjualan (Studl Kasus Pada Po.Puspa Jaya Group) Di Bandar Lampung - Wayan Saputra; Farida Efrianti (Peneliti.net, 2023)
There are many companiesi that are engagedi the field ofin Passenger transportation services in Bandar Lampung whichi becomei competitors for. POPuspa Jaya Group of course .- strategies business theseThe survey is aimed at identifying the Strengths, Weaknesses, Opportunities and Threats of the OD business. Puspa Jaya Group. The survey method used is descriptive using qualitative data types. Data collection was carried out using library and field studies with techniques data, and documentation. In the survey analysis was used and the SWOT matrix was used to formulate and determine OD business development tactics. Puspa Jaya Group in Bandar Lampung. The assessment of weighti, ratingi and scorei fori strategy factor cani result in 3 andi scorei for external strategy. 1.3